Casa Minuto, Ramos Mejía
Vivienda centrada es la sala de estar, con una gran terraza que acompaña un jardín de dimensiones limitadas.
Keywords: BERRETTA, HORACIO; ARGENTINA; BUENOS AIRES (PROV); RAMOS MEJIA; VIVIENDAS UNIFAMILIARES